Entrepreneurship Education and Business Students’ Entrepreneurial Intention: Implications for Social Science Education - Gretchen Bangguiyac (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study investigates the influence of entrepreneurship education on the entrepreneurial intention of college business students at Kalinga State University. The research examined students’ perceptions of four dimensions of entrepreneurship education: entrepreneurial university climate, entrepreneurship curricula, entrepreneurial knowledge, and entrepreneurial skills. Methodology: This study employed a quantitative research approach, particularly a descriptive–correlational design. Data were collected from 48 graduating Bachelor of Science in Entrepreneurship students using total population sampling. A standardized questionnaire with established validity and reliability was administered to gather responses from the students. Main Findings: Entrepreneurial knowledge (M = 4.38, SD = 0.575) and entrepreneurship curricula (M = 4.32, SD = 0.653) received the highest ratings, followed by entrepreneurial skills (M = 4.24, SD = 0.657). Entrepreneurial university climate, while rated lowest, still obtained a positive evaluation (M = 4.01, SD = 0.740). Entrepreneurial intention was likewise high (M = 4.28, SD = 0.690), reflecting strong entrepreneurial aspirations among students. Pearson correlation analysis revealed that entrepreneurship curricula (r = 0.443, p = 0.002) and entrepreneurial skills (r = 0.431, p = 0.002) were significantly and positively associated with entrepreneurial intention. In contrast, the entrepreneurial university climate and entrepreneurial knowledge were not statistically significant. Novelty/Originality of this study: Previous studies primarily examined entrepreneurship education as a single construct influencing entrepreneurial intention. The author has not found research that simultaneously tests entrepreneurial university climate, curricula, knowledge, and skills within Economic Education and social learning frameworks. This study integrates these dimensions to explain how educational processes shape economic behavior and entrepreneurial intention.